Community-based tourism initiatives and their contribution to sustainable local development - Walkowski, Marinês da Conceição; Pires, Paulo dos Santos; Tricárico, Luciano Torres (Goodwood Publishing, 2019)
Purpose: The research question/purpose is to know which CBT initiatives are still active in Brazil, as well as the challenges that exist in the sustainable local development perspective. Research Methodology: We based this exploratory research on extensive bibliographic research on the theme in addition to field observations. As a research strategy, we used the multiple case study involving two Brazilian initiatives: the Rede Tucum, in Ceará, and the Acolhida na Colônia, in Santa Catarina. Results: The main results showed that despite the difficulties associated with the CBT development, both projects have remained due to the strong articulation between the leaders, partnerships with educational institutions and entities, the methodology maintenance provided by the project’s technical team, and the diversification of tourism offer based on sustainability actions. Limitations: The limitation was access to fishing communities. Contribution: The contribution will assist in advancing studies with this theme and in tourism disciplines of local base. Keywords: Community-based tourism, Sustainable local development, Rede Tucum, Acolhida na Colônia